Use of Vegetable Powders in the Control of Acanthoscelides obtectus Say (Coleoptera: Bruchidae) in Stored Bean Grains - Baldin, Edson L. L.; Prado, João Paulo M.; Christovam, Rafael S.; Dal Pogetto, Mário H. F. A. (BioAssay, 2009)
The effects of eleven vegetable powders applied in bean grains were evaluated on the biology of Acanthoscelides obtectus Say. The amount of 0.3g of powders mixed to 10g of grains of bean genotype IAC – Carioca was placed into plastic boxes with four couples of bean weevils during a 7-day period. Twenty five days after infestation, we started recording the oviposition and the number of emerged adults in each treatment. At the end of the adult emergence period, the dry weight of adults, the weight of consumed grains and period of development (egg-adult) were evaluated. The powders of Baccharis trimera Less., Mentha pulegium L. and Coriandrum sativum L. reduced the oviposition of A. obtectus, but do not affect the development of bean weevil larvae. The highest oviposition was obtained with bean grains mixed to powders of Leonurus sibiricus L.. The lowest weight of A. obtectus adults was obtained from bean grains treated with Azadirachta indica A. Juss. possibly due to the occurrence of feeding deterrence to A. obtectus larvae.